Repair Process Impairment by Pseudomonas aeruginosa in Epithelial Tissues: Major Features and Potential Therapeutic Avenues - Ruffin, Manon; Brochiero, Emmanuelle (Frontiers in Cellular and Infection Microbiology, 2019)
Epithelial tissues protecting organs from the environment are the first-line of defense against pathogens. Therefore, efficient repair mechanisms after injury are crucial to maintain epithelial integrity. However, these healing processes can be insufficient to restore epithelial integrity, notably in infectious conditions. Pseudomonas aeruginosa infections in cutaneous, corneal and respiratory tract epithelia are of particular concern because they are the leading causes of hospitalizations, disabilities and deaths worldwide. P. aeruginosa has been shown to alter repair processes, leading to chronic wounds and infections. Because of the current increase in the incidence of multi-drug resistant isolates of P. aeruginosa, complementary approaches to decrease the negative impact of these bacteria on epithelia are urgently needed. Here, we review the recent advances in the understanding of the impact of P. aeruginosa infections on the integrity and repair mechanisms of alveolar, airway, cutaneous and corneal epithelia. Potential therapeutic avenues aimed at counteracting this deleterious impact of infection are also discussed.